2022
DOI: 10.3390/en15113872
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Life Cycle Assessment Modelling of Densified Fuel Production from Various Biomass Species

Abstract: This work presents new data on the life cycle impact assessment of various lignocellulosic biomass types in Mexico. A comparative life cycle assessment model of biomass densification systems was conducted. An integrated approach that incorporated various process variables, such as technology and variations in feed properties, within the analysis was employed to evaluate the environmental impact of producing 1 MJ of energy-containing densified fuel. The results show that the densification unit and curing (fuel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For example, Disni Gamaralalage et al reported that using Malaysian palm kernel shells to generate electricity was more beneficial than using native wood chips [7]. Rukayya Ibrahim Muazu et al used LCA to conclude that the densification unit and curing (fuel drying) had the highest impact on the life cycle's operational energy and the total life cycle energy [8].…”
Section: Applications Of Lcamentioning
confidence: 99%
“…For example, Disni Gamaralalage et al reported that using Malaysian palm kernel shells to generate electricity was more beneficial than using native wood chips [7]. Rukayya Ibrahim Muazu et al used LCA to conclude that the densification unit and curing (fuel drying) had the highest impact on the life cycle's operational energy and the total life cycle energy [8].…”
Section: Applications Of Lcamentioning
confidence: 99%
“…If bioenergy is consumed instead of fossil fuels, carbon neutrality can be achieved (Yang et al, 2019) (Paraschiv and Paraschiv, 2023). There has been an increase of interest in lignocellulosic feedstock due to the growing focus on bioenergy (Fusi et al, 2021); (Muazu et al, 2022). Biomass has advantages such as renewability and diversification, making it a potential source of primary energy having approximately 10 11 Gt of supply potential (Majada et al, 2021).…”
Section: Need For Renewable Energy Planning Based On Crop Residuesmentioning
confidence: 99%
“…Any stage of a product or service life cycle, comprising material acquisition, manufacturing, distribution logistics, use and resource circulation [11], as shown in Figure 1, can emit GHG. The stages can occur worldwide and interact with other supply chains globally [12][13][14]. A comprehensive LCA accounts for the impacts of all interacting global supply chains allocated to the concerned products, activities or services [11,15].…”
Section: Introductionmentioning
confidence: 99%